Comparison of the effectiveness in remineralization of the initial lesion of dental caries using two application protocols and two brands of 5% fluoride varnish - Santamaria García, Rocío Alejandra; Mendoza Ibañez, Alma Jeaneth; Maldonado Avelar, Erika Cristabel; Escobar de González, Wendy Yesenia; Carranza Mendoza, Iván; Rivera Ventura, José Osmín; Rivas Cartagena, Francisco Jose; Arbizú Trigueros, Regina Guadalupe; Gómez de Martínez, Aida Maricela; Aguirre Escobar, Guillermo Alfonso (Revista Minerva, 2022)
Introduction: The initial dental caries is the first clinical manifestation of dental caries produced by enamel´s mineral lost, different fluoride varnish brands stimulated its remineralization and prevent the decay advancement. Objective: To compare the effectiveness of two protocols and two fluoride varnish brands in the initial caries lesión remineralization. Materials and Methods: Experimental, double-blind study with two parallel controlled groups. The sample was of 68 teeth with initial caries, according to diagnosis with criteria ICDAS II (01 and 02) and with degree of demineralization between 13-24nm according to DIAGNOdent pen®. Two brands of fluoride varnish 0.5% were used, with two application protocols and 6 controls were performed in each one. It was tabulated using Microsoft Word Excel and the statistical test of Levene and T-test was used using the software SPSS v.18. Results: All groups showed a decrease in the time course of the degree of demineralization of incipient caries. In five of the six controls the Sig (p-value) was greater than p = 0.05, showing that there is no significant difference between the marks. The final difference between protocols was 16 (50.0%) teeth remineralized for protocol A and 12 (31.57%) teeth for protocol B. Conclusions: application of fluoride varnish favored remineralization over time, but there is no significant difference of effectiveness between both protocols and fluoride varnish brands.